Prevalence of microalbuminuria and its association with glycemic control in type 2 diabetic patients: a cross sectional study at Kathmandu Medical College - Karki, Prabin Kumar; Timalsina, Santosh; Chalise, Sanat; Yadav, Anita; Bhattarai, Ashish Kumar (Journal of Chitwan Medical College, 2019)
Background: Diabetes mellitus has become one of the biggest health problems of this era. The resultant microvascular and macrovascular complications add to significant amount of morbidity and mortality. Urine microalbumin is considered as an early marker for microvascular complications among diabetic patients. The aim of this study was to find out the prevalence of microalbuminuria among type 2 diabetic patients attending Kathmandu Medical College and its relation with glycemic control, age, sex, duration of diabetes. Methods: A total of 208 previously diagnosed type 2 diabetic patients attending medical outpatient department of Kathmandu Medical College, Sinamangal were included in the study over a period of 1 year (October 2017 - September 2018). Fasting and 2-hour postprandial venous blood for blood glucose and HbA1c measurement and early morning urine sample (after overnight fast) was collected for detection of microalbuminuria. Statistical analysis was done using SPSS version 23. Results: The prevalence of microalbuminuria among the study population (mean age: 54.22 ± 11.76 years, mean HbA1c: 7.62 ± 1.53 %) was 42.8%. Microalbuminuria had significant correlation with HbA1c and duration of diabetes (p